Effects of Pre-Hatch Thermal Programming on Internal Organ Development of Crossbred Chickens in The First Week Post-Hatch - Andri, Faizal; Marwi, Filoza; Arif, Ani Atul; Sudjarwo, Edhy (TERNAK TROPIKA Journal of Tropical Animal Production, 2024)
This study evaluated the effects of pre-hatch thermal programming on internal organ development of crossbred chickens in the first week post-hatch. A total of 200 fertile eggs from a crossbreed of male local chickens and commercial laying hens were used in this study. The average egg weight was 62.76 ± 4.40 g with a coefficient of variation was 7.01%. The eggs were randomly distributed into four treatment groups, each with five replicates (10 eggs per replicate). The treatments were T0: standard incubation maintained at 37.50°C throughout the entire incubation period (control); T1: standard incubation with a 6-hour daily increase to 38.50°C from days 10-18, T2: standard incubation with a 6-hour daily increase to 39.50°C from days 10-18, and T3: standard incubation with a 6-hour daily increase to 40.50°C from days 10-18. After hatch, the chicks were reared for a week and evaluated for internal organ development. The results showed that there were no significant differences among treatments (P>0.05) for all measured variables, including the absolute weights (g) and relative percentages (%) of the internal organ. The absolute weight of the heart, liver, proventriculus, gizzard, and intestine were ranged from 0.69 to 0.84, 2.68 to 2.93, 0.74 to 0.87, 6.48 to 7.05, and 7.94 to 8.42 g, respectively. Whereas, the relative weight of the heart, liver, proventriculus, gizzard, and intestine were ranged from 0.89 to 1.12, 3.46 to 3.79, 0.95 to 1.13, 8.29 to 9.11, 10.24 to 10.82%, respectively. It could be concluded that pre-hatch thermal programming can be considered a safe strategy without compromising internal organ development of crossbred chickens in the early post-hatch period.